(untitled) (Research, Society and Development, 2022)
Bulk solid stockpile reclaiming by gravity through bottom reclaimers at the base is a common method in the industry, as it is inexpensive, although it requires large plant floor areas. The complexity of actual particulate systems and the configuration of the recovery system often makes the quantitative prediction of dead volumes after recovery difficult, especially if historical or experimental data are not available. Incremental advances in design criteria and innovation can result in remarkable gains, due to the large amount of bulk materials currently handled. Research in this field, therefore, is still of importance. This article addresses the live volume fraction of conical stockpile recovered through underground hoppers and conveyor belt, comparing bench-scale empirical data with indirect measurements by drone-based aerial photogrammetry and mathematical modeling, via analytical geometry and computational simulation employing cellular automata. The results have shown excellent statistical adherence of the estimates both via photogrammetry and mathematical modeling.